2019
DOI: 10.4174/astr.2019.97.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Urinary transglutaminase 2 as a potent biomarker to predict interstitial fibrosis and tubular atrophy of kidney allograft during early posttransplant period in deceased donor kidney transplantation

Abstract: Purpose Transglutaminase type 2 (TG2) is an extracellular matrix crosslinking enzyme with a pivotal role in kidney fibrosis. We tested whether quantification of urinary TG2 may represent a noninvasive method to estimate the severity of kidney allograft fibrosis. Methods We prospectively collected urine specimens from 18 deceased donor kidney transplant recipients at 1-day, 7-day, 1-month, 3-month, and 6-month posttransplant. In addition, kidney allograft tissue specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Besides the urine markers in this study, urine N-acetyl-beta-glucosamynidase, tissue transglutaminase (tTG), transforming growth factor-β (TGF-β), Matrix metalloproteinases (MMPs), and so on are also the research hotspots. 17 , 18 , 19 , 20 This suggests that a single marker is not enough to monitor the occurrence and outcome of AKI accurately, and combined markers may be more effective. For example, urine IL-18 combined with KIM-1 is considered to have the best diagnostic value for AKI that already exists, and urine NGAL combined with IL-18 is the best marker for the diagnosis of early AKI, while urine Nacetyl-beta-glucosamynidase combined with KIM-1 and IL-18 is an ideal marker for the prognosis of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the urine markers in this study, urine N-acetyl-beta-glucosamynidase, tissue transglutaminase (tTG), transforming growth factor-β (TGF-β), Matrix metalloproteinases (MMPs), and so on are also the research hotspots. 17 , 18 , 19 , 20 This suggests that a single marker is not enough to monitor the occurrence and outcome of AKI accurately, and combined markers may be more effective. For example, urine IL-18 combined with KIM-1 is considered to have the best diagnostic value for AKI that already exists, and urine NGAL combined with IL-18 is the best marker for the diagnosis of early AKI, while urine Nacetyl-beta-glucosamynidase combined with KIM-1 and IL-18 is an ideal marker for the prognosis of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…TG2 is excreted at increased levels into the urine of patients with renal fibrosis (20). To investigate whether this increase is specific to patients with fibrotic remodeling of the kidneys, or also observed upon systemic fibrotic remodeling, we analyzed TG2 levels in urine samples from 30 SSc patients and 20 healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Increased urinary TG2 levels depict allograft inflammation or fibrosis in kidney transplant patients [ 56 ], and in CKD patients, urinary TG2 levels could be considered a potential biomarker for CKD progression [ 21 ]. Previous studies have demonstrated the mechanisms underlying TG2 associated-ECM accumulation.…”
Section: Discussionmentioning
confidence: 99%